Asymptomatic Prenatal Zika Virus Infection and Congenital Zika Syndrome. (7th April 2018) - Paixao, Enny S; Leong, Wei-Yee; Rodrigues, Laura C; Wilder-Smith, Annelies
Abstract: To investigate to what extent asymptomatic vs symptomatic prenatal Zika virus infections contribute to birth defects, we identified 3 prospective and 8 retrospective studies. The ratio varied greatly in the retrospective studies, most likely due to recruitment and recall bias. The prospective studies revealed a ratio of 1:1 for asymptomatic vs symptomatic maternal Zika infections resulting in adverse fetal outcomes.